Thin Teflon-like films for eliminating adhesion in released polysilicon microstructures - Smith, Bradley K.; Sniegowski, Jeffry J.; LaVigne, Glenn; Brown, Craig (Sensors and actuators. A. Physical., 1998)
This paper presents a method for depositing thin Teflon-like films to eliminate adhesion or suction in released polysilicon microstructures. A commercial plasma reactor is used in direct and remote plasma modes with commercially available trifluoromethane (CHF 3) to deposit thin hydrophobic films around and under released microstructures. Hard, uniform, Teflon-like films which penetrate into undercuts beneath structures have been produced. Thus far, surfaces beneath gears as large as 1600 μm diameter with a gap of 2.0 μm are hydrophobic after being exposed to plasma treatment. These Teflon-like coatings have been shown to reduce the coefficient of friction from 1.0 to 0.07.